Experimental study on the seismic performance of L-shaped column composed of concrete-filled steel tubes frame structures. (November 2015) - Zhou, Ting; Jia, Yumeng; Xu, Minyang; Wang, Xiaodun; Chen, Zhihua
Abstract: This paper experimentally investigated the behavior of specially shaped columns composed of concrete-filled steel tube frames (SCFST frames) subjected to constant axial load and cyclically varying flexural load. Three specimens with two storeys and a single span were tested. The effects of axial compression ratio and the beam-to-column stiffness ratios on the behavior (i.e., stiffness, strength, ductility, and energy dissipation) of SCFST frames were studied. The failure modes of the frames were studied. The hysteretic curve shapes of these three specimens were smooth and full, and the skeleton curves both have gently descending stages, which represent suitable ductility and energy dissipation ability. The load carrying capacity and stiffness decreased with the decrease in axial compression ratio, but the energy dissipation ability and ductility increased and the stiffness degeneration decreased. The load carrying capacity and stiffness decreased with the increase in beam-to-column stiffness ratio, but the energy dissipation and deformation abilities increased. Furthermore, a finite element analysis was conducted to simulate the behavior of SCFST frames. Test results agreed with the results of the finite element analysis. Graphical abstract: Highlights: The hysteretic curve, skeleton curves and seismic parameters represent a good seismic behavior of this structure. With the decrease of axial compression ratio, bearing capacity decreased, but energy dissipation ability increased. With the increase of beam-to-column stiffness ratio, bearing capacity decreased, but energy dissipation ability increased. Reasonable FEM model was proposed.